Jordanian Mothers’ Acceptance of their Handicapped Children - Al-Qaryouti, Ibrahim (Jordan Journal of Educational Sciences, 2008)
The study aimed to investigate the degree of mothers’ acceptance of their handicapped children in Jordan. The sample of the study consisted of 405 mothers of handicapped children enrolled in various special education schools and centers, of whom 167 were mothers of deaf children, 96 mothers of blind children, 65 mothers of cerebral palsy (C P)children, and 77 mothers of mentally retarded children. A questionnaire consisting of (43) items was used to measure the degree of the mother’s acceptance of her disabled child. A test was carried out to check validity and reliability of the questionnaire.The results of the study revealed statistically significant differences in mothers’ acceptance of their disabled children related to the type of disability in favor of hearing and visual disabilities vis-à-vis mental retardation.The results also showed that there are significant differences in mothers’ acceptance of their disabled children related to the degree of hearing impairment and gender in favor of the severity, females and the interaction between gender and age.Regarding (CP) disability, the degree of mothers’ acceptance was in favor of children ranging from 6-12 years old compared to children less than 6 years, and above 18 years old. No differences were found regarding visual and mental disabilities. The researcher recommends that further study of other cases like autism, hyper-activity and learning disabilities be conducted